Preliminary findings on the role of high-frequency (5Hz) rTMS stimulation on M1 and pre-SMA regions in Parkinson's disease - Hanoğlu, Lütfü; Sarıcaoğlu, Mevhibe; Toprak, Güven; Helvacı Yılmaz, Nesrin; Yuluğ, Burak (Elsevier Ireland Ltd, 2020)
It has been already shown that the motor symptoms of the Parkinson's Disease (PD) have been improved with high frequency rTMS although there is no consensus on the most suitable target brain localization for a maximal therapeutic efficacy. Here, we aimed to compare the therapeutic effect of high frequency (5Hz) rTMS stimulation on primary motor cortex (M1) and pre-supplementary (pre SMA) regions in patients with PD who were still on pharmacological treatment. The study included right-hand dominant16 patients with PD (5 females, 11 males) with demographically and clinically similar characteristics which were randomly assigned to group 1 (n=8) and group 2 (n=8) and received left M1 and the left pre-SMA rTMS procedure, respectively. Total and sequential motor scores of the Unified Parkinson's Disease Rating Scale (UPDRSmotor) were applied to all patients at the baseline and the patients were re-evaluated under the same clinical conditions one week after the end of the sessions. Comparisons of the UPDRS-motor scores between two groups yielded significant improvements after the rTMS on pre-SMA compared to M1 (M1 p=0.14; pre-SMA p=0.01). which were especially significant for the bradykinesia (p=0.04) and axial score related items (p=0.01). This is the first study that shows the effect of rTMS on pre-SMA and it appears to be a promising option in the treatment of PD.
Keywords: High Frequency Rtms; M1 Stimulation; Parkinson's Disease; Pre-SMA Stimulation